EXPERIENCES OF PEOPLE LIVING WITH HIV/AIDS IN SURVIVING LIFE - Bagas Biyanzah Drajad Pamukhti; Meira Erawati; Muflihatul Muniroh; Nur Setiawati Dewi (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Fear of contracting HIV in the community causes discrimination and stigma to people living with HIV/AIDS (PLWHA) because people still consider HIV/AIDS taboo. Many of the sufferers struggle to reveal their HIV status to others, but they get negative results such as rejection, stigmatization and even discrimination which can be a high psychological burden. Stigma and discrimination against PLWHA are the main obstacles to achieving a good quality of life. Objectives: This study is intended to explore the in-depth experiences of people living with HIV/AIDS in surviving life. Methods: This research is a phenomenological case study. The sample in this study amounted to three people who were recruited from Healthy Loving Care Foundation Semarang City. The sample was determined using a purposive sampling technique according to the inclusion criteria, that is age 20 and 50 years, diagnosed with HIV/AIDS, conscious, cooperative, not experiencing cognitive, hearing and speech disorders, willing to participate in the study by signing the informed consent. The data was collected by in-depth online interviews and then recorded in transcripts and analyzed using Amedeo Giorgi's data analysis technique. Results: This study showed that participants experience adversity due to HIV/AIDS but the participants get out of their slump by accepting their illness, taking treatment, finding a support system and becoming a positive people. The participants also in living their lives keep their illness a secret to survive so as not to experience bad stigma or discrimination. The results of this study reveal one main theme, Experiences of People living with HIV in Surviving life. Conclusion: This study found the support received by participants and the response of participants to their condition as an effort to survive their lives.